Perbandingan Prinsip Good Corporate Governance Pada Bank Konvensional Dan Bank Syariah Dalam Sistem Hukum di Indonesia - Nasution, Juliana; Nafisah, Hana; Elvina, Ayu; Harahap, Aswan Nawawi; Utami, Novidia (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to explain the comparison of the principles of Good Corporate Governance in conventional banks and Islamic banks in Indonesia. The method used in this research is normative legal research. The results of the study explain that the application of the principles of Good Corporate Governance in conventional banks and Islamic banks is the same, because it refers to the 'Guidelines for Good Corporate Governance in Indonesian Banking' issued by the National Committee on Governance Policy. The difference is that the principles of Good Corporate Governance in Islamic banks are strictly regulated in Article 34 Paragraph (1) of Law Number 21 of 2008. Another difference lies in the sharia principles used by Islamic banks because apart from being fostered and supervised by the Financial Services Authority, Islamic banks It is also supervised by the National Sharia Council of the Indonesian Ulema Council (MUI) in general and the Sharia Supervisory Board in particular. This is evidence of the existence and significant development of Islamic banking in the national banking system.